Efektifitas Latihan Fisik Terhadap Resiko Jatuh Pada Lansia: Systematic Review - Alviana, Fifi; Mulyani, Sri; Azuma, Anindita Paramastuti (Jurnal Ilmiah Kesehatan, 2017)
Purpose: The purpose of this systematic review was analyze the article to provide accurate and best information about the effectiveness of physical exercise against the risk of falling in the elderly. Methods: Researchers searched one electronic databases for relevant articles published between 2012 and 2017. Data were collected using inclusion and exclusion criteria. The Joanna Briggs Institute Instrument was used to evaluate the quality of the identified articles. Results: There were 5 articles analyzed in a systematic review. The movement in physical exercise consists of heating, hearing movement. The length of time required for physical exercise were 30 minutes. Physical exercises can be applied in communities, hospitals, nursing homes and home care. Conclusion: This systematic review showed the effectiveness of physical exercise can affect the risk of falls in the elderly. Key Words: elderly, risk of falls, physical exercise.